Exploring employee satisfaction in the hospitality industry: An IPA approach to Como Uma Canggu hotel - Anak Agung Ayu Mirah Kencanawati; Ni Nyoman Supiatni; Lily Marheni; Zurul Aisya Osman; Md. Emran Uddin; Sandeep Kumar; Basu Dev Lamichhane (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study aims to evaluate the level of employee job satisfaction at CUC Hotel and to identify areas requiring improvement using the Importance Performance Analysis (IPA) method. Job satisfaction is a crucial factor in enhancing employee productivity and retention, particularly in the hospitality industry, which relies heavily on human resources. The research employs a quantitative descriptive approach with data collected through a structured questionnaire. The population of the study consists of all employees at CUC Hotel, with a sample of 67 respondents selected through probability sampling techniques. Data were analysed using descriptive statistics to determine the average scores for each indicator, followed by Importance Performance Analysis to map the satisfaction attributes into quadrants based on their importance and performance. The IPA results reveal four main attributes located in Quadrant I (high importance, low performance) of the Cartesian diagram, specifically: promotion opportunities, co-worker relationships, and supervisor relationships. These findings suggest that while these attributes are considered highly important by employees, their current performance is insufficient and requires managerial attention. The overall conformity level reached 85.56%, indicating that, in general, the job satisfaction of employees at CUC Hotel is relatively good. The study recommends that management prioritize improvement efforts on attributes within Quadrant I to maintain and enhance employee satisfaction consistently and effectively.